2017 Spokane, Washington July 16 - July 19, 2017 2017
DOI: 10.13031/aim.201700269
|View full text |Cite
|
Sign up to set email alerts
|

<i>Antibiotics and antibiotic resistant bacteria and genes in northeastern dairy manure management systems � Project overview and preliminary findings from an 11 farm case study</i>

Abstract: Modern U.S. dairies use antibiotics primarily for disease treatment and prevention. Consequently, antibiotic residues, antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARG) present in dairy manure may potentially enter the environment and contribute to the spread of antibiotic resistance (AR). Working cooperatively with 11 production dairies in three states (NY, PA, MD) our objective is to investigate the efficacy of existing on-farm manure management practices (e.g. long-term storage, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Unlike tetracyclines, the widely used β-lactam antibiotics are more soluble and seemingly less persistent (Table 2). In our study of over 80 fresh manure samples collected from 11 northeastern US dairy operations over a 15-mo period, no β-lactam residues were detected in any manure samples, despite the common use of penicillins and cephalosporins on these dairy operations (Oliver et al, 2017). To our knowledge, the only study of dairy cows to measure a β-lactam residue found very low levels of cephapirin and only in pre-excreted cecal samples and cow urine collected with a catheter (Ray et al, 2014).…”
Section: Antibiotic Residues and Metabolites In Dairy Manurementioning
confidence: 51%
“…Unlike tetracyclines, the widely used β-lactam antibiotics are more soluble and seemingly less persistent (Table 2). In our study of over 80 fresh manure samples collected from 11 northeastern US dairy operations over a 15-mo period, no β-lactam residues were detected in any manure samples, despite the common use of penicillins and cephalosporins on these dairy operations (Oliver et al, 2017). To our knowledge, the only study of dairy cows to measure a β-lactam residue found very low levels of cephapirin and only in pre-excreted cecal samples and cow urine collected with a catheter (Ray et al, 2014).…”
Section: Antibiotic Residues and Metabolites In Dairy Manurementioning
confidence: 51%